Edukasi dan Demonstrasi Teknik Menyusui Meningkatkan Kualitas Laktasi Pada Ibu dan Bayi - Naomi Rawatina Dongoran; Islah Wahyuni (WOMB Midwifery Journal, 2025)
Proper breastfeeding is an essential physiological practice for the health of mothers and babies, especially in the early stages of life. However, successful breastfeeding is not only determined by timing, but also by the mother's knowledge, experience, and skills in applying proper breastfeeding techniques. This study aims to describe continuous midwifery care for Mrs. S through the application of breastfeeding techniques from pregnancy to the postpartum period as a lactation preparation effort. The uniqueness of this study lies in the application of education and demonstration of breastfeeding techniques continuously across midwifery service periods and objective evaluation using several assessment instruments. The care was provided in Simataniari Village, Hasundutan District, North Sumatra, in 2025, covering the final trimester of pregnancy, childbirth, postpartum, newborn, neonate, and family planning services. The results showed a significant increase in mothers' knowledge (score of 10 to 16), breastfeeding self-efficacy based on BSES-SF (score of 36 to 59), breastfeeding skills based on LATCH scores (score of 6 to 10), and understanding of breastfeeding techniques (score of 23 to 39). No complications such as sore nipples or breast engorgement were found during the lactation process. These findings indicate that support combined with education and demonstrations of breastfeeding techniques is effective in supporting a comfortable, safe, and sustainable lactation process. The application of this method is recommended as a strategy to increase breastfeeding success in midwifery services.